Atividades de marketing verde em práticas socioambientais das grandes indústrias do Paraná - Lopes, Valéria Neder (2011)
Lately, its being frequent to find companies involved in social issues and due to this reason is possible to notice a mobilization of those organizations towards less aggressive environmental practices. The Green Marketing fits within this concept which should be connected with both social and environmental practices aiming the development of products and marketing activities more sustainable, strengthening the company's image to create a differential in their brands. The objective of this study was to evaluate if Green Marketing practices used by the large industries affiliated the FIEP (Federação das Indústrias do Estado do Paraná) are aligned with their social practices and environmental management. In order to develop this work, a survey on the existing literature about Green Marketing and Social / Environmental Management were made, as well as evaluating what green marketing activities are used by the enterprises, their social / environmental practices and understand whether there is a correlation between those variables or not. A transversal descriptive quantitative research was prepared to support this study and data were collected thru questionnaires obtained from 48 large companies registered as part of FIEP association. The results obtained indicate that great part of the organizations evaluated have a formal marketing department, having also their own environmental management system. Most of the companies also host social and environmental projects but data show a very poor utilization of these practices as a differential argument to position themselves in the market.